2022
DOI: 10.1002/ana.26413
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging or Computed Tomography for Suspected Acute Stroke: Association of Admission Image Modality with Acute Recanalization Therapies, Workflow Metrics, and Outcomes

Abstract: Objective To examine rates of intravenous thrombolysis (IVT), mechanical thrombectomy (MT), door‐to‐needle (DTN) time, door‐to‐puncture (DTP) time, and functional outcome between patients with admission magnetic resonance imaging (MRI) versus computed tomography (CT). Methods An observational cohort study of consecutive patients using a target trial design within the nationwide Swiss‐Stroke‐Registry from January 2014 to August 2020 was carried out. Exclusion criteria included MRI contraindications, transferred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 41 publications
(111 reference statements)
2
16
0
1
Order By: Relevance
“…We retrieved 3133 unique records, of which 200 were included in the review (Figure 1). All reasons for excluding records after full-text review are given in eAppendix 6 in Supplement 1.…”
Section: Resultsmentioning
confidence: 99%
“…We retrieved 3133 unique records, of which 200 were included in the review (Figure 1). All reasons for excluding records after full-text review are given in eAppendix 6 in Supplement 1.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the time delay due to advanced imaging, several studies showed that advanced imaging led to longer door-to-puncture 12,18,19 and door-to-needle times. 35 In 1 report, time delays to treatment might not be as critical for functional outcome after thrombectomy in patients who present in the extended time window (6-24 hours) compared with patients in the early time window. 27 In this survey, 78% of respondents believed that a delay of 20 minutes or less was acceptable to obtain advanced imaging prior to thrombectomy.…”
Section: Discussionmentioning
confidence: 96%
“…95,96 The use of MRI as the primary modality in patients presenting with AIS has increased over the years. 97 MRI is as accurate as CT for the detection of hyperacute hemorrhage using susceptibility-weighted images (SWI). 98 MRI is also more sensitive than CT to detect subtle hemorrhagic changes within the ischemic lesion.…”
Section: Mri-based Imagingmentioning
confidence: 99%
“…The use of MRI as the primary modality in patients presenting with AIS has increased over the years [ 97 ]. MRI is as accurate as CT for the detection of hyperacute hemorrhage using susceptibility-weighted images (SWI) [ 98 ].…”
Section: Mri-based Imagingmentioning
confidence: 99%